Toeing the Line: Erick Hawkins in Cold War America - Marissa Catherine Ajamian (The Journal of Undergraduate Research, 2018)
While many dance artists pushed against the normative culture of the Cold War, Erick Hawkins, a modern dance choreographer, rarely did. Through the creation of the Hawkins technique and his choreographic aesthetic, Hawkins upheld the normalcy policies of the Cold War using his ideals of beauty and “natural,” kinesthetically correct, dance. Because Hawkins was falling in line with Cold War policies, he failed to receive the recognition and renown of fellow choreographers. He was unwilling to stay within the artistic parameters that critics and the U.S. Department of State created for modern dance. By upholding normalcy policies but also rejecting dance elements the accepted canon required, Hawkins’ falls between the lines of mainstream and the vanguard of modern dance. This has caused Hawkins’ work to be rejected in concert dance because he disregarded the values of fellow artists, critics, and the State Department’s accepted views on dance. Not having the recognition from any of these sources has caused Hawkins to have been omitted from conversations of dance modernism. While Hawkins has been minimized in the canon, his influence and impact are significant to understanding that modern dance is not solely restricted to historical definitions of the canon or the vanguard.